The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1007/s00383-010-2585-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of the retrograde colonic enema in children with spina bifida: is it inferior to the antegrade continence enema?

Abstract: Our results suggest that retrograde colonic enema was not inferior to Malone antegrade continence enema on fecal continence. We recommend considering retrograde colonic enema prior to introduction of Malone antegrade continence enema in children with spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…4 The initiating event for the deterioration of the patient's fecal control was the FEC 100 chemotherapy. The FEC 100 regimen has been shown to be an efficacious adjuvant treatment for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…4 The initiating event for the deterioration of the patient's fecal control was the FEC 100 chemotherapy. The FEC 100 regimen has been shown to be an efficacious adjuvant treatment for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of up to 10% of patients with chronic constipation does not sufficiently respond to dietary changes, oral laxatives, rectal enemas, or retrograde lavage . While retrograde colon lavage can be efficacious, it is time‐consuming and often large volumes are needed, resulting in considerable patient discomfort. When all conservative measures fail, surgical treatments such as appendicostomy, ileostomy with colonic exclusion, or segmental or total colectomy are considered .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] In recent years, transanal irrigation (TAI) has become a popular option in the management of NBD due to its successful results and acceptable safety profile. [17][18][19][20][21][22][23] TAI has been suggested as a first-line therapy for children with neuropathic bowel dysfunction who do not respond to conservative medical therapy. 9 Moreover, TAI constitutes an integral part of the total endoscopic and anal irrigation management (TEAM) approach in children with noncompliant NB.…”
Section: Introductionmentioning
confidence: 99%
“…Matsuno and colleagues retrospectively compared 25 patients with spina bifida and fecal incontinence using either TAI or MACE. 23 They found no difference in the achievement of fecal continence between the 2 groups and concluded that TAI is not inferior to MACE. Our prospective results support their recommendation in considering TAI prior to the introduction of MACE in children with spina bifida.…”
mentioning
confidence: 96%
See 1 more Smart Citation